Is family social exclusion associated with child motor and socioemotional development delay? A cross‐sectional exploratory study - Clariana Vitória Ramos De Oliveira; Cláudia Nery Teixeira Palombo; Joshua Jeong; Katherine Maria Solís Cordero; Elizabeth Fujimori (Wiley, 2023)
Abstract Aim The objective was to identify if family social exclusion is associated with child motor and social development delay in Southeastern Brazil. Design A cross‐sectional study was conducted using data from a sample of 348 children under 3 years, proportional to the number of children registered in the primary care centres of the municipality. Methods Child development was measured using the "Developmental Surveillance Instrument" which was developed by the Ministry of Health in Brazil and is used for public health nurses and clinicians in their practice. An index was used to evaluate social exclusion. Results The prevalence of child motor and socioemotional developmental delay was 27.6% and 17.2%, respectively. Children in the most social excluded group were more likely to have delayed motor development (OR = 3.4; 95% CI = 1.14; 10.55) and socioemotional developmental delay (OR = 3.9; 95% CI = 1.05; 9.02) than children in the least social excluded group.